Inflammatory Dendritic Cells Contribute to Regulate the Immune Response in Sickle Cell Disease - Sesti-Costa, Renata; Borges, Marina Dorigatti; Lanaro, Carolina; Albuquerque, Dulcinéia Martins de; Saad, Sara Terezinha Olalla; Costa, Fernando Ferreira (Frontiers in Immunology, 2021)
Sickle cell disease (SCD), one of the most common hemoglobinopathies worldwide, is characterized by a chronic inflammatory component, with systemic release of inflammatory cytokines, due to hemolysis and vaso-occlusive processes. Patients with SCD demonstrate dysfunctional T and B lymphocyte responses, and they are more susceptible to infection. Although dendritic cells (DCs) are the main component responsible for activating and polarizing lymphocytic function, and are able to produce pro-inflammatory cytokines found in the serum of patients with SCD, minimal studies have thus far been devoted to these cells. In the present study, we identified the subpopulations of circulating DCs in patients with SCD, and found that the bloodstream of the patients showed higher numbers and percentages of DCs than that of healthy individuals. Among all the main DCs subsets, inflammatory DCs (CD14+ DCs) were responsible for this rise and correlated with higher reticulocyte count. The patients had more activated monocyte-derived DCs (mo-DCs), which produced MCP-1, IL-6, and IL-8 in culture. We found that a CD14+ mo-DC subset present in culture from some of the patients was the more activated subset and was mainly responsible for cytokine production, and this subset was also responsible for IL-17 production in co-culture with T lymphocytes. Finally, we suggest an involvement of heme oxygenase in the upregulation of CD14 in mo-DCs from the patients, indicating a potential mechanism for inducing inflammatory DC differentiation from circulating monocytes in the patients, which correlated with inflammatory cytokine production, T lymphocyte response skewing, and reticulocyte count.